Trace of Islamic Educational Thought - Farninda Aditya (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
Book Review: Erwin Mahrus and Syamsul Kurniawan, Trace of Islamic Educational Thought, Pontianak: STAIN Pontianak Press . Don’t judge a book by its cover, goes the popular saying. It is probably true as the cover does not always represent the contents of the book. However, this one is an exception. Without looking at the title, one will immediately think of: the important figures in Islamic education.